2021
DOI: 10.1111/hae.14431
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inhibitor eradication by primary immune tolerance induction in severe haemophilia A with high responding inhibitors

Abstract: Background Immune tolerance induction (ITI) is the only proven strategy to eradicate factor VIII inhibitors in patients with haemophilia A (HA). Aim To identify patients and treatment options with the highest chance of inhibitor eradication by primary ITI. Patients and methods In the frame of the Italian ITI Registry, carried out from 1995 to 2015 (last follow‐up 2018), 137 primary ITI courses in severe HA patients (90/137 with poor prognosis) were analysed for predictors of outcome (complete/partial response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Peyvandi et al 18 reported that patients with large deletions had the lowest success rate (1/8) of ITI, and a similar finding was revealed that large deletions in F8 were associated with ITI unresponsiveness 7 . The Italian ITI registry observed that small insertions/deletions and missense mutations were linked to complete inhibitor eradication and a shorter time to ITI success 8–9 . This study showed that the patients carrying non–high‐risk mutations associated with inhibitor development were more likely to be successful in ITI and resulted in a shorter time to success.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Peyvandi et al 18 reported that patients with large deletions had the lowest success rate (1/8) of ITI, and a similar finding was revealed that large deletions in F8 were associated with ITI unresponsiveness 7 . The Italian ITI registry observed that small insertions/deletions and missense mutations were linked to complete inhibitor eradication and a shorter time to ITI success 8–9 . This study showed that the patients carrying non–high‐risk mutations associated with inhibitor development were more likely to be successful in ITI and resulted in a shorter time to success.…”
Section: Discussionsupporting
confidence: 57%
“…7 The Italian ITI registry observed that small insertions/deletions and missense mutations were linked to complete inhibitor eradication and a shorter time to ITI success. [8][9] This study showed that the patients carrying nonhigh-risk mutations associated with inhibitor development were more likely to be successful in ITI and resulted in a shorter time to success. Interestingly, patients carrying high-risk variants were associated with higher inhibitor titers, including historical peak titers, pre-ITI titers, and peak titers during ITI, as well as higher rates of combined immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations